Eucalyptus torelliana - its Successful Trial and Introduction at New Forest, Dehra Dun - Hingorani, G. R.; Pant, H. C. (Indian Forester, 1970)
The paper gives in brief the results of Eucalyptus torelliana F.V.M., its successful trial and introduction at the Forest Research Institute, Dehra Dun. Its trial in areas possessing climatic conditions similar to Dehra Dun as well as in wet tropical zones is suggested in view of its being a potential raw material for paper industry.